Vade Mecum in ERCP, a roadmap to success: Tips from experts for excelling in ERCP - Teles de Campos, Sara; Arvanitaki, Marianna; Boskoski, Ivo; Deviere, Jacques (Endoscopy International Open, 2024)
Background and study aims Training in endoscopic retrograde cholangiopancreatography (ERCP) is operator-dependent and traditionally, the apprenticeship model, in which experts are considered to be role models, has been adopted for it. The aim of this study was to develop a practical guide compiling tips from experts to help guide trainees to succeed in ERCP.Methods A web-based survey was created to understand the professional development of ERCP experts, the investments they made, the obstacles they overcame, and the quotes that guided their professional life. ERCP experts worldwide were invited to participate.Results Fifty-three experts (of 71; 74.6%) from 24 countries answered the survey. Experts started ERCP training early (average age 31 years; range, 24–52 years) and it often was combined with training for endoscopic ultrasound. A long training period (average 21 months; range, 3–120 months) was needed to achieve competence, frequently in another department, and it was commonly complemented with research in the field (76.5%). “Time and practice” were the most worthwhile investments they made to achieve success. “Sports” were an area outside endoscopy frequently considered to be important to acquire the skills necessary to excel in ERCP. “Lack of dedicated time for training” and “peer competition” were the biggest obstacles the experts faced. Several pieces of advice were given to the experts, such as to be resilient, careful, patient, responsible, and hard-working. “Personal life” was mentioned as an undeniably crucial factor for achieving long-term success that should not be forgotten.Conclusions This survey is the first to provide insight regarding the professional trajectory of renowned ERCP experts worldwide, providing valuable recommendations to help trainees excel in ERCP.
Keywords: Quality and logistical aspects; Training; Pancreatobiliary (ERCP/PTCD); Performance and complications